Destination boardroom : secrets of a discrete profession - executive search unveiled - Eijick, Eelco van (Emerald Publishing Limited, 2024)
In Destination Boardroom seasoned executive search consultant and board member Eelco van Eijck introduces readers to the mysterious world of headhunting. Its practitioners play a pivotal role in finding and positioning leaders for today's challenging business and public arenas. Based on 20 years' expertise and input from leading executives and management thinkers, Eelco shares honest and intriguing insights into the journey to the boardroom, answering key questions such as: How is today's leadership talent really sought and found? Executive search is by nature discrete and mysterious. What do its practitioners actually do? What are the true mechanisms behind the journey to the boardroom? Leadership is being profoundly re-shaped by the quest for sustainability and the tsunami of digitization. Given this, what traits will set the future-ready apart? How can hiring organizations maximise their chances of a successful hire (and rise above board politics)? How is digitization changing executive search (and what won't change?) How are successful modern organizations governed, designed, and managed? In what ways must executive search evolve to earn the status of a true profession and be fit for the 21st century? Destination Boardroom is the ideal read for any business looking to improve their hiring or any executive wishing to get noticed and advance their career to the next level.